Highly strong and sensitive bilayer hydrogel actuators enhanced by cross-oriented nanocellulose networks. (7th July 2022) - Liu, Wei; Geng, Lihong; Wu, Jianming; Huang, An; Peng, Xiangfang
Abstract: Temperature-responsive bilayer hydrogel actuator with anisotropic structure in mutually perpendicular directions was successfully prepared, where poly (N-isopropyl acrylamide)/cellulose nanofiber (PNIPAM/CNF) double network hydrogel was applied as the top layer, and poly (acrylamide-co-acrylic acid)/cellulose nanofiber (PAM-AA/CNF) double network hydrogel served as the bottom layer. The cross-oriented structure of the two hydrogel layers contributed to the superior actuation ability and mechanical performance of the bilayer hydrogel actuator. Consequently, the hydrogel actuator could quickly lift a weight with 70 times of their own weight with a high bending speed of 10.21 (°/s). Furthermore, the tensile strength and elongation at break of the hydrogel actuator reached 729.5 ± 21.5 KPa and (406.5 ± 11.3) % respectively. After further cross-linking by Fe 3+, the tensile strength of the actuator reached 3.86 MPa. With excellent mechanical performance and actuation ability, the resulting bilayer hydrogel showed a promising application potential as artificial soft tissue materials and intelligent actuators. Graphical abstract: Image 1 Highlights: Temperature-responsive bilayer hydrogel actuator was successfully prepared. Both layers of the actuator were anisotropic double network hydrogels. The orientation directions of the two hydrogel layers were mutually perpendicular. The bending speed of the bilayer hydrogel actuator reached 10.21 (°/s). After cross-linking by Fe 3+, the strength of hydrogel actuators reached 3.86 MPa.